Lack of benefit from combined therapy with gonadotropin-releasing hormone analog (GnRHa) and recombinant human growth hormone (rhGH) in patients with early or precocious puberty - Virú-Loza, Manuel André (2021)
Study conclusions: The overall analysis does not indicate benefit of combination therapy (gonadotropin-releasing hormone analog [GnRHa] + recombinant human growth hormone [rhGH]) versus GnRHa alone, rhGH alone, or no treatment. However, there are benefits to a greater or lesser extent in certain subpopulations. Critical comment: The article is relevant as there was no previous meta-analysis on combination therapy. On the other hand, it is important since combination therapy involves the use of rhGH, which can be expensive, difficult to adhere to, and lead to adverse effects. Furthermore, the general conclusion of the article - do not use combination therapy - is applicable. However, the assessment of publication bias and selective reporting is lacking, and there are secondary conclusions that require better explanation. The present critical review does not find sufficient evidence to suggest that combination therapy may be effective in any subpopulation.